2016
DOI: 10.4172/2167-7948.1000200
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer Metabolism: A Review

Abstract: Metabolic dysregulation within the tumor microenvironment (TME) is critical to the process of tumorigenesis in various cancer types. Thyrocyte metabolism in papillary and anaplastic thyroid cancer, however, remains poorly characterized, and studies analyzing the role of multicompartment metabolism in thyrocyte oncogenesis are sparse. We present a review of the current knowledge on cellular metabolism in non-cancerous and cancerous thyroid tissues, focusing on the monocarboxylate transporters MCT1 and MCT4, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…These results might be interpreted as representative of the shift from aerobic toward anaerobic glycolysis. The decrease of LDH activity in anaplastic carcinoma compared to that in differentiated carcinoma (Gill et al, 2016) and has been confirmed by Valvona et al (2016) who stated that the activity enzymes of the citric acid cycle were inversely proportionate to the mitotic activity. Furthermore, Slavov et al (2014) studied the relationship between the metabolisms of cell division and tumor growth.…”
Section: Discussionmentioning
confidence: 71%
“…These results might be interpreted as representative of the shift from aerobic toward anaerobic glycolysis. The decrease of LDH activity in anaplastic carcinoma compared to that in differentiated carcinoma (Gill et al, 2016) and has been confirmed by Valvona et al (2016) who stated that the activity enzymes of the citric acid cycle were inversely proportionate to the mitotic activity. Furthermore, Slavov et al (2014) studied the relationship between the metabolisms of cell division and tumor growth.…”
Section: Discussionmentioning
confidence: 71%
“… 16 , 88 It has a low affinity for lactate, and its primary function is to transport intracellular lactate out of the cell. 89 Studies have reported that MCT4 expression is mainly regulated by cell metabolism and the hypoxic environment. 90 In addition to these two transporters, MCT8, a member of the MCT family, is related to TH transport and is also distributed in the thyroid gland.…”
Section: Monocarboxylate Transporters (Mcts) and Metabolism In Tcmentioning
confidence: 99%
“…Studies have confirmed that the expression levels of MCT1 and MCT4 are increased to varying degrees in different types of TC. 89 , 99 , 100 Pioneering researchers conducted an immunohistochemical analysis of orthotopic xenograft tumors and clinicopathological specimens and found that MCT1 was highly expressed relative to MCT4 in anaplastic TC (ATC). 87 Nahm et al conducted a similar experiment with the clinicopathological specimens of 566 patients with TC and immunohistochemically analyzed the expression of proteins related to tumor glycolysis.…”
Section: Monocarboxylate Transporters (Mcts) and Metabolism In Tcmentioning
confidence: 99%
“…The incidence of thyroid cancer, one of the most common endocrine tumors, is increasing worldwide. Malignant thyroid cancer can be classified into four main types comprising papillary, follicular, medullary, and anaplastic thyroid cancer (ATC) [ 1 , 2 ]. ATC is one of the most lethal malignancies owing to poor differentiation and invasion into the surrounding tissues, such as the trachea [ 3 ].…”
Section: Introductionmentioning
confidence: 99%